Data Encryption, Authentication and Key Predistribution Schemes for Wireless Sensor Networks - Alexanian, Ara; Aslanyan, Hakob; Soghoyan, Armen (Mathematical Problems of Computer Science, 2021)
This paper investigates some security aspects of wireless sensor networks. Particularly symmetric encryption, authentication and key predistribution schemes are proposed. Encryption and authentication schemes are based on a secret key which is a table of strong generators of a permutation group (as per Sims algorithm). The ciphertext of a plaintext of size N is a single permutation over n = 2N + 1 elements. Encryption/Decryption processes are simple and easy to perform for a wireless node with limited abilities. Key predistribution scheme deals with all the node and network limitations and requirements existing in wireless sensor networks and gives a secure key predistribution scheme under the assumption that nodes are not physically captured for t0 time after being deployed, where t0 is time necessary for invoking the key establishment phase of proposed scheme, which is in practice should be some seconds.